Two new species of Sabatieria (Nematoda, Comesomatidae) from Golfo Nuevo, Chubut (Argentina) - de Ward, Catalina T. Pastor (Zootaxa, 2003)
Two new Comesomatidae species from the Gulfs of San José and San Matías, Chubut province of Argentina are described. Sabatieria flecha sp. n. is characterized by the particular shape of the dorsal distal end of the spicule, smaller spicule length (47 μm; 1.5 anal body diameter), number of weakly cuticularised supplements (12), size of amphids with two and a half turns, short body length (1260 μm), values of a (36) and b (7,8) and tail shape with 1/3 cylindrical part. Sabatieria sanjosensis sp. n. is characterized by a long body length (3000 μm), large value for a (82) and tail shape with 1/2 cylindrical part.